Optical signature of Weyl electronic structures in tantalum pnictides TaPn (Pn= P, As) - Kimura, Shin-Ichi; Yokoyama, Hiroko; Watanabe, Hiroshi; Sichelschmidt, Joerg; Suess, Vicky; Schmidt, Marcus; Felser, Claudia (Physical Review B, 2017)
To investigate the electronic structure of Weyl semimetals TaPn (Pn= P, As), optical conductivity [σ(ω)] spectra are measured over a wide range of photon energies and temperatures, and these measured values are compared with band calculations. Two significant structures can be observed: a bending structure at ω∼85 meV in TaAs, and peaks at ω∼ 50 meV (TaP) and ∼30 meV (TaAs). The bending structure can be explained by the interband transition between saddle points connecting a set of W2 Weyl points. The temperature dependence of the peak intensity can be fitted by assuming the interband transition between saddle points connecting a set of W1 Weyl points. Owing to the different temperature dependence of the Drude weight in both materials, it is found that the Weyl points of TaAs are located near the Fermi level, whereas those of TaP are further away.
CRIS-Team Scopus Importer:2022-04-14